Pengaruh Kompetensi Akuntansi dan Keterampilan Mengoperasikan Komputer Terhadap Hasil Belajar Komputer Akuntansi MYOB Siswa di SMK St. Gabriel Maumere - Maharani, Christiani Dimarcia Sri; Mitan, Wilhelmina; Goo, Emilianus Eo K. (Universitas Nusa Nipa Maumere, 2025)
The purpose of this study is to determine the effect of accounting competence and computer operating skills on the learning outcomes of MYOB accounting computer subjects among students of SMK St. Gabriel Maumere. This research is a quantitative study using an associative strategy approach, in which the sampling technique applied is purposive sampling with a total sample of 59 respondents. The research data were collected by distributing questionnaires to the respondents. Data analysis was conducted using multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS) Statistics 25 software. The results of this study indicate that, partially, accounting competence has a significant effect on the learning outcomes of MYOB accounting computer subjects, and computer operating skills also have a significant effect on these learning outcomes among students of SMK St. Gabriel Maumere. Meanwhile, simultaneously, accounting competence and computer operating skills together have a significant effect on the learning outcomes of MYOB accounting computer subjects among students of SMK St. Gabriel Maumere.